An Urgent Need for Legal Safeguards for Freelancers in Vietnam - Duong, Thi Minh Hang (International Journal of Law and Public Policy (IJLAPP), 2025)
The rapid expansion of Vietnam’s freelance workforce has outpaced the development of legal protections for freelancers, which highlights the urgent need for a coherent and inclusive legal approach to safeguard self-employed individuals in Vietnam’s evolving economy. This article examines the legal landscape governing freelancers in Vietnam, identifying critical gaps in current regulations that hinder the protection of freelancers’ rights with a focus on Labor Law and Civil Law. Drawing on international practices from Japan, Germany, and the Netherlands, the study proposes some recommendations to ensure fair treatment and strengthen Vietnam’s legal protections for self-employed workers.